Adjunctive Subantimicrobial Dose Doxycycline in the Treatment of Chronic Periodontitis in Type 2 Diabetic Patients: A Unique Combination Therapy - Gomaa Marwa Abdelhakim; Guindy Hoda Mohamed El; El-Zamrany Enas Arafa (Balkan Stomatological Society, 2018)
Background/Aim: To evaluate the effectiveness of combination therapy including subantimicrobial dose doxycycline (SDD) and locally delivered doxycycline (LD) as adjuncts to scaling and root planing (SRP) in the treatment of chronic periodontitis in patients with type 2 diabetes mellitus (T2DM). Material and Methods: Forty patients with controlled T2DM (HbA1c ≤7%) and chronic periodontitis were selected. They were randomly divided into two groups, twenty patients each: Test group (TG, n=20) patients was treated with combination therapy of full mouth SRP, LD gel 10% and SDD 20 mg twice daily for 6 months. Control group (CG, n=20) patients was treated with full mouth SRP only. The periodontal parameters were recorded at baseline, 3, 6 and 9 months and included periodontal probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BOP). Gingival crevicular fluid (GCF) samples were collected and a quantitative measurement of matrix metalloproteinase-8 (MMP-8) was carried out by using Enzyme-Linked Immunosorbent Assay (ELIZA) at baseline, 3, 6 and 9 months. Results: Statistically significant reduction in all clinical parameters (PPD, CAL, and BOP) was observed at TG over CG at 3, 6, and 9 months (p<0.05). Moreover, combination therapy provided significant reductions in the amount of GCF MMP-8 for the TG compared to CG at 3, 6, and 9 months evaluation period (p<0.05). Conclusions: Combination therapy including SRP, SDD, and LD, provided significantly greater clinical benefits than SRP alone in the treatment of chronic periodontitis in patients with controlled T2DM.